2017
DOI: 10.18632/oncotarget.21095
|View full text |Cite
|
Sign up to set email alerts
|

ING4expressing oncolytic vaccinia virus promotes anti-tumor efficiency and synergizes with gemcitabine in pancreatic cancer

Abstract: With no effective treatments available for most pancreatic cancer patients, pancreatic cancer continues to be one of the most difficult malignancies to treat. Oncolytic virus mediated-gene therapy has exhibited ubiquitous antitumor potential. In this study, we constructed a novel oncolytic vaccinia virus harboring the inhibitor of growth family member 4 gene (VV-ING4) to investigate its therapeutic efficacy alone or in combination with gemcitabine against pancreatic cancer cells in vitro and in vivo. ING4 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Our previous studies have demonstrated that oVV-ING4 indeed blocks cell cycle in G2 phase. 33 Despite cytarabine is an S-phase-specific chemotherapeutic drug, its synergistic anticancer effect with oVV-ING4 can be observed in Figure 5 . We speculate that this may be related to the complex action mechanism of cytarabine.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that oVV-ING4 indeed blocks cell cycle in G2 phase. 33 Despite cytarabine is an S-phase-specific chemotherapeutic drug, its synergistic anticancer effect with oVV-ING4 can be observed in Figure 5 . We speculate that this may be related to the complex action mechanism of cytarabine.…”
Section: Discussionmentioning
confidence: 99%
“…34 Recombinant VACV has shown therapeutic effects in several murine tumor models, including those of glioblastoma, pancreatic cancer, and melanoma. [35][36][37][38] Interestingly, we found that both WT and recombinant VACV were less replicative in the murine triple-negative breast cancer (TNBC) cell line 4T1, which shows high levels of TTP, 39 both in vitro and in vivo. Furthermore, TNBC cells from different species differ in terms of TTP expression, which affects the replication of recombinant VACV.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, Smac is expressed at a lower level in pancreatic tumors (10 of 10) compared with normal pancreas (data not shown). Several clinical studies have reported synergistic antitumor activity of the co-treatment with oVV and chemotherapy or radiation therapy ( 30 , 31 ). Additionally, it has been suggested that the route of combination of oVV with cytotoxic chemotherapies is another factor in potentiating the effects of oVV and optimizing the therapy ( 32 ).…”
Section: Discussionmentioning
confidence: 99%